2021
DOI: 10.1001/jamanetworkopen.2021.32917
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinician and Patient Factors and Completion of Telemedicine Appointments Using Video

Abstract: IMPORTANCETelemedicine provides patients access to episodic and longitudinal care. Policy discussions surrounding future support for telemedicine require an understanding of factors associated with successful video visits. OBJECTIVE To assess patient and clinician factors associated with successful and with failed video visits. DESIGN, SETTING, AND PARTICIPANTS This was a quality improvement study of 137 846 scheduled video visits at a single academic health system in southeastern Wisconsin between March 1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 28 publications
3
32
1
Order By: Relevance
“…We hypothesized that important clinical information could be missed via audio-only connections, and video visits were considered both the institutional and the Medicare standard to replace in-person visits, with limited reimbursement given for audio-only visits. 19 Subsequent studies have used a similar method to identify unsuccessful visits, 6 , 20 and video visits, rather than telephone only, were rated as highly as in-person visits. 21 Inability to complete audio and visual assessments may be associated with some of the negative outcomes we observed or may be a surrogate for a more disadvantaged patient population at risk of inferior outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that important clinical information could be missed via audio-only connections, and video visits were considered both the institutional and the Medicare standard to replace in-person visits, with limited reimbursement given for audio-only visits. 19 Subsequent studies have used a similar method to identify unsuccessful visits, 6 , 20 and video visits, rather than telephone only, were rated as highly as in-person visits. 21 Inability to complete audio and visual assessments may be associated with some of the negative outcomes we observed or may be a surrogate for a more disadvantaged patient population at risk of inferior outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These disparities have been observed in many other digital health interventions, including video visits and telemedicine. 49 , 50 , 51 …”
Section: Discussionmentioning
confidence: 99%
“…For instance, several studies have found that older age, Black race, Hispanic ethnicity, Medicaid insurance coverage, and living in zip codes with low broadband access are associated with the following: (1) lower probability of using video-based care, and (2) greater conversion of video visits to telephone visits. 2 – 4 Focusing this type of intervention on digitally vulnerable populations could be one simple, system-based way to bridge the digital divide. Moreover, a recent study found that practice- (38%) and clinician-level (26%) factors drove more of the variation in video visit use than patient-level factors (9%) 3 —illustrating that health care providers and systems have significant control over the modality through which they deliver care.…”
Section: Discussionmentioning
confidence: 99%